Successful surgical intervention in traumatic carotid artery thrombosis after a motor vehicle accident: a case report - Görkem Yiğit (Journal of Trauma and Injury)
Blunt carotid artery injury can lead to impaired brain perfusion due to ischemic stroke and thromboembolic events. To reduce the risk of potential neurological complications, it is critical to determine the diagnosis and management protocol as quickly as possible after a detailed clinical examination. This report presents successful surgical treatment of a young male patient who developed a traumatic left common carotid artery thrombosis after a motor vehicle accident.